Effect of bi-linear thickness variation on vibration of the non- homogeneous orthotropic (S-C-S-C) triangular plate with the bi-linear temperature variations - Kavita; Manoj Kumar Dhiman; Vijyeta Verma (Utilitas Mathematica, 2025)
In present paper a simple model is presented to study the effect of non-homogeneity on vibration of triangular plate with bilinear thickness variation. Thermal Induced vibration of these plates has been taken as two dimensional temperature distributions. Poisson ratio is assumed to vary bilinearily for non-homogeneity of the plate material. Using separation of variables method, the governing differential equation has been solved. The time period corresponding to the first two modes of vibration has been calculated for a simply supported-clamped triangular plate for various values of aspect ratio, thermal constant, taper constant and skew angle.